Validity of two wheelchair-mounted devices for estimating wheelchair speed and distance traveled - Karinharju, K. S.; Gomersall, S. R.; Clanchy, K. M.; Trost, S. G.; Yeo, L. T.; Tweedy, S. M. (Adapted Physical Activity Quarterly, 2023)
This study evaluated the validity of two wheelchair-mounted devices—the Cateye® and Wheeler—for monitoring wheelchair speed and distance traveled. Speed estimates were validated against a calibrated treadmill at speeds from 1.5 to 10 km/hr. Twenty-five wheelchair users completed a course of known distance comprising a sequence of everyday wheelchair activities. Speed estimate validity was very good (mean absolute percentage error = 5%) for the Wheeleri at all speeds and for the Cateye at speeds >3 km/hr but not speeds <3 km/hr (mean absolute percentage error > 20%). Wheeleri distance estimates were good (mean absolute percentage error < 10%) for linear pushing activities and general maneuvering but poor for confined-space maneuvering. Cateye estimates were good for continuous linear propulsion but poor for discontinuous pushing and maneuvering (both general and confined space). Both devices provided valid estimates of speed and distance for typical wheelchair-based exercise activities. However, the Wheeleri provided more accurate estimates of speed and distance during typical everyday wheelchair activities.